TEACHING FACTORY LEARNING MANGEMENT TO IMPROVE THE QUALITY OF FASHION STUDENT' PRODUCTS AT SMK NEGERI 1 SANGATTA UTARA - Darajat, Sakia; A Azainil; Akhmad; U Haryaka; Widyatmike, GM; L Komariyah (International Journal of Cultural and Social Science, 2026)
The quality of products produced by students has not fully met the standards and needs of the business and industrial world. Therefore, the implementation of Teaching Factory learning as a production-based learning approach in vocational schools is needed. This study aims to describe the management of Teaching Factory learning in improving the quality of student products in the Department of Fashion Design and Production at SMK Negeri 1 Sangatta Utara. This study used a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Research informants consisted of the principal, vice principal for curriculum, head of department, production unit coordinator, productive teachers, and students. The results show that Teaching Factory learning management is implemented based on the 7M components: Man, Money, Material, Machine, Method, Market, and Minute, integrated into management functions of planning, organizing, implementing, and supervising. Planning is carried out through curriculum synchronization with industry needs and the application of a block system. Organizing involves clear task distribution, while implementation engages students in the full production process according to industry procedures. Supervision is conducted through monitoring and quality control with industry partners. The implementation of Teaching Factory improves product neatness, technical precision, production time efficiency, and conformity with market standards. Thus, it contributes positively to improving the quality of student products.